2019
DOI: 10.1111/bph.14583
|View full text |Cite
|
Sign up to set email alerts
|

1,2,3,4,6‐Penta‐O‐galloyl‐β‐d‐glucose modulates perivascular inflammation and prevents vascular dysfunction in angiotensin II‐induced hypertension

Abstract: Background and Purpose Hypertension is a multifactorial disease, manifested by vascular dysfunction, increased superoxide production, and perivascular inflammation. In this study, we have hypothesized that 1,2,3,4,6‐penta‐O‐galloyl‐β‐d‐glucose (PGG) would inhibit vascular inflammation and protect from vascular dysfunction in an experimental model of hypertension. Experimental Approach PGG was administered to mice every 2 days at a dose of 10 mg·kg−1 i.p during 14 days of Ang II infusion. It was used at a final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…We also have observed that vascular impairment independent of the endothelium appears in the aorta of LA mice. A similar effect was observed in an angiotensin II-induced model of hypertension [ 38 ]. We believe that this effect is mostly related to guanylyl cyclase function.…”
Section: Discussionsupporting
confidence: 77%
“…We also have observed that vascular impairment independent of the endothelium appears in the aorta of LA mice. A similar effect was observed in an angiotensin II-induced model of hypertension [ 38 ]. We believe that this effect is mostly related to guanylyl cyclase function.…”
Section: Discussionsupporting
confidence: 77%
“…Inflammation and the immune response were clustered in the black and turquoise modules of dilated PVAT samples. Using microarray data from AAA tissue, researchers have found that immune (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…PVAT of Ang II-induced hypertensive mice displayed a higher number of immune cells such as macrophages, leukocytes, T cells, and dendritic cells. Ang II induction also enhances RANTES, MCP-1, and CCL3 expression in the periaortic PVAT and the aortic wall of the mice [ 61 , 146 ]. Moreover, activation of angiotensin II type 1 receptor (AT1R) in PVAT promotes vascular inflammation and endothelial dysfunction [ 147 ].…”
Section: Hypertensionmentioning
confidence: 99%